A Case of Progressive Multifocal Leukoencephalopathy in a Fumaric Acid-Treated Psoriasis Patient With Severe Lymphopenia Among Other Risk Factors. (1st August 2021) - Engel, Sinah; Molina Galindo, Lara S; Bittner, Stefan; Zipp, Frauke; Luessi, Felix
Progressive multifocal leukoencephalopathy (PML) is a potentially fatal condition caused by a brain infection with JC polyomavirus (JCV), which occurs almost exclusively in immunocompromised patients. Modern immunosuppressive and immunomodulatory treatments for cancers and autoimmune diseases have been accompanied by increasing numbers of PML cases. We report a psoriasis patient treated with fumaric acid esters (FAEs) with concomitant hypopharyngeal carcinoma and chronic alcohol abuse who developed PML. Grade 4 lymphopenia at the time point of PML diagnosis suggested an immunocompromised state. This case underscores the importance of immune cell monitoring in patients treated with FAEs, even more so in the presence of additional risk factors for an immune dysfunction.